REHABILITATION MECHANISM FOR VICTIMS OF RAPE - S Hutapea, Novelina Mutiara; Gultom, Sarles; Nababan, Bramayana; Telaumbanua, Chris Jolly Gunanta; Sirait, Kevin Sturges (Inspiring Law Journal, 2025)
The perpetrator of rape should be burdened with the responsibility to, among other things, provide compensation (restitution), treat, and bear the costs incurred for the victim's mental or psychological recovery from the traumatic experience. If the perpetrator is unable to carry out these obligations, then the obligation becomes the responsibility of the state and society. Meanwhile, perpetrators who are unable to fulfill their obligations are burdened with substitute punishment in the form of imprisonment as a subsidiary punishment. The question is, in which law should these provisions be regulated? Because all criminal justice processes culminate in the Criminal Procedure Code, the first provision regarding the imposition of responsibility for compensation must be expressly stated in the Criminal Procedure Code. Furthermore, of course in the Criminal Code as the umbrella of national criminal law, which is then also regulated in laws that are lex specialis. The form of compensation can be submitted to the court through the LPSK by the victim of the crime of rape, their family, or their attorney, which can be in the form of material and immaterial. Material compensation in the form of restitution and compensation, and immaterial compensation can be in the form of assistance, namely psycho-social rehabilitation. In providing compensation, the priority is psycho-social rehabilitation, because restoring a person's condition cannot be done through material provision alone